The Impact of Cigarette Butts on Soil and Water Health: A Case Study in Urban Areas - Indasah; Armen Patria; Dini Henriyanto (Journal Of Nursing Practice, 2024)
Background: The increasing prevalence of cigarette butt littering in urban environments poses significant environmental challenges, particularly concerning soil and water health. This issue is not merely an aesthetic concern; it has profound implications for ecosystems, public health, and urban management. As cities expand and populations grow, the volume of cigarette waste continues to rise, leading to a multitude of environmental repercussions that warrant a closer examination. Purpose: This study aimed to investigate the impact of cigarette butts on soil quality and water contamination in urban areas, focusing on specific case studies within metropolitan regions. Method: Employing a mixed-methods approach, the research includes quantitative analysis of soil and water samples collected from various urban sites, alongside qualitative assessments through surveys of local residents regarding their perceptions of cigarette butt pollution. Results: Preliminary findings indicate that the leachates from cigarette butts contain harmful chemicals that adversely affect soil microbial activity and water quality. Conclusion: This paper discusses the implications of these findings for urban environmental management and public health policies